Real time quantification of mixed ion and electron transfer associated with the doping of poly(3-hexylthiophene). Issue 18 (21st April 2022) - Thakur, Ratul Mitra; Easley, Alexandra D.; Wang, Shaoyang; Zhang, Yiren; Ober, Christopher K.; Lutkenhaus, Jodie L.
Abstract : Real-time effects of mass transfer and electrochemical doping on the electronic properties of P3HT. Abstract : Conjugated polymers have promising applications in electronics and energy storage due to the polymer's tunable conductivity and redox activity. For example, the conductivity of poly(3-hexylthiophene) (P3HT) is heavily dependent upon the doping level and the dopant type. This feature becomes especially important when considering P3HT or similar conjugated polymers for devices that require switching between electronic states (conductive vs. insulating). In this study, the mechanism of mixed ion-electron transfer studied using electrochemical quartz crystal microbalance with dissipation monitoring (EQCM-D) is discussed. During cyclic voltammetry and galvanostatic charge–discharge experiments, the mass change of a P3HT film is monitored in real time. Distinct mass transfer regions are quantified as a function of doping level and potential, which are then correlated to changes with in situ conductance and spectroelectrochemical response. To identify the time scale at which the doping reaction transitions from kinetic to diffusion control, electrochemical impedance spectroscopy is coupled with EQCM-D. This work gives valuable insight into the nature of mixed ion–electron transfer, including its time scale, as it relates to the electronic properties of P3HT.